Sport physiology biomechanical parameters of running technique in the distance of sprinter finalists of the World Championship - Balandin, S. I.; Balandina, I. Yu.; Zayko, D. S.; Dmitriev, I. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to compare the spatio-temporal, kinematic and angular characteristics of the running technique over the distance of the strongest sprinters in the world at 100 and 200 m.